Zukunft Lernwelt Hochschule Perspektiven und Optionen für eine Neuausrichtung - Stang, Richard; Becker, Alexandra (De Gruyter, 2020)
Based on the findings of the college learning environment research project, this book includes a range of articles on the future of colleges focusing on organization, didactics, digital structures and physical learning or teaching spaces. In the future, a critical task will be establishing colleges as unified or integrated learning environments.